Effect of non-condensable gas on submerged steam jet condensation in a narrow pipe. (25th January 2023) - Chen, Xianbing; Yang, Luopeng; Zhang, Wenke; Ma, Xiaoxu; Zhang, Lili; Wang, Yubo; Zhang, Jingzhi; Tian, Maocheng
Highlights: A visualization study on steam–air jet in subcooled water flow was conducted. The effect of air on four typical steam plume shapes was analyzed. A new correlation was proposed to predict the dimensionless penetration length. The effect of air on average heat transfer coefficient was studied. Abstract: A visualization study was performed to investigate the effect of non-condensable gas on stable submerged steam jet condensation in water flow in a narrow pipe. The direct contact condensation (DCC) characteristics including jet plume shapes, dimensionless penetration length and average heat transfer coefficient were analyzed in a wide range of water flow subcooling, Reynolds number of water flow and steam–air mixture flow rates. As four different steam plume shapes for pure steam jet in subcooled water flow in a pipe were reported in the previous research, the effect of non-condensable gas on the four steam plume shapes was investigated by introducing a certain amount of air into steam. In the current study, the submerged steam–air mixture jet behavior was investigated through direct visualization techniques. The effect of non-condensable gas on jet plume shapes was recorded by using a high speed camera. The gas–liquid interface and the dimensionless penetration length was obtained by digital image processing method implemented by a MATLAB subroutine. Then the average heat transfer coefficient was calculated based on thermal equilibrium of gas–liquid interface. In the experiment, the gas mass flux at nozzle exit was within 320–780 kg/m 2 /s, with no more than 1 % non-condensable gas. The results indicated that the non-condensable gas plays an important role on the gas–liquid interface, jet penetration length and heat transfer coefficient. It was found that when 1 % non-condensable gas was mixed with steam jet, the dimensionless penetration length was extended by 16–70 %, and the average heat transfer coefficient decreased by 12–50 %. Based on the force-balance of jet plume, a new quantitative correlation for the steam–air mixture jet penetration length was proposed. The predicted jet penetration length agrees well with the experimental measured values.